Application of Student Standardized Patients Simulation in Clinical Practice Teaching of Rehabilitation Therapy - Guohua YU; Weiming SUN; Lang SHUAI; Yin YAN (康复学报)
Objective:To explore the training effects of student standardized patient simulation in clinical practice teaching for rehabilitation students.Methods:A total of 66 clinical students of rehabilitation therapies were randomly divided into observation group and control group, with 34 cases and 32 cases in each group. The control group used the traditional teaching approach, and the observation group used the student standardized patient simulation (SSP) approach, the theoretical results, practical skills, and teaching results were compared between the two groups.Results:Comparison of the rehabilitation assessment of swallowing function, rehabilitation treatment and medical record writing scores and the practical skills test scores between the two groups, the observation group showed higher scores than those of the control group. Questionnaire survey results showed that the scores of students' medical history collection ability, communication and expressive ability, learning enthusiasm and initiative, ability of combining theory with practice, and professional literacy ability were all better than those of the control group, with statistically significant differences (P<0.05).Conclusion:The application of SSP simulation teaching approach is helpful to improve the students' enthusiasm and initiative, enhance the practical skill operation level, and strengthen the students' ability to connect theory with practice.